Computational aerodynamics: Advances and challenges. (4th February 2016) - Drikakis, Dimitris; Kwak, Dochan; Kiris, Cetin C.
ABSTRACT: Computational aerodynamics, which complement more expensive empirical approaches, are critical for developing aerospace vehicles. During the past three decades, computational aerodynamics capability has improved remarkably, following advances in computer hardware and algorithm development. However, most of the fundamental computational capability realised in recent applications is derived from earlier advances, where specific gaps in solution procedures have been addressed only incrementally. The present article presents our view of the state of the art in computational aerodynamics and assessment of the issues that drive future aerodynamics and aerospace vehicle development. Requisite capabilities for perceived future needs are discussed, and associated grand challenge problems are presented.